2005
DOI: 10.1007/bf03026334
|View full text |Cite
|
Sign up to set email alerts
|

Absorptiometric assessment of muscle-bone relationships in humans: reference, validation, and application studies

Abstract: This report summarizes some preliminary absorptiometric (DXA, QCT/pQCT) studies from our laboratory, supporting the following assumptions. 1. In Homo sapiens at all ages, natural proportionality between DXA-assessed bone mineral mass (bone mineral content, BMC) and muscle mass (lean mass, LM) of the whole body or limbs is specific for ethnicity, gender, and reproductive status, but not for body weight, height, or body mass index. 2. This proportionality is sensitive to many kinds of endocrine-metabolic perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Muscle size was consistently the dominant predictor of bone content and strength in the radius, whereas results in the tibia were less consistent, with muscle size and body mass varying in relative predictive value. Our results agree with previous evidence of the close relationship between MCSA and bone strength estimates in the arm 20,21 and leg, 18,[22][23][24] and with DXA-derived data suggesting that this relationship differs between the upper and lower limbs. 25,26 Our study adds to this literature by illustrating the site-specificity of the relationship between pQCT-derived bone measures of strength and local muscle area within the forearms and lower legs of the same individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Muscle size was consistently the dominant predictor of bone content and strength in the radius, whereas results in the tibia were less consistent, with muscle size and body mass varying in relative predictive value. Our results agree with previous evidence of the close relationship between MCSA and bone strength estimates in the arm 20,21 and leg, 18,[22][23][24] and with DXA-derived data suggesting that this relationship differs between the upper and lower limbs. 25,26 Our study adds to this literature by illustrating the site-specificity of the relationship between pQCT-derived bone measures of strength and local muscle area within the forearms and lower legs of the same individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Relationships between muscle and bone have been investigated in the whole body, 19 arm, 20,21 and leg. 18,[22][23][24] In addition, limb-specific associations between muscle force and bone mineral content in pubertal female individuals 25 and between lean mass and bone mineral content in adults 26 have been examined using dual-energy X-ray absorptiometry (DXA). However, to our knowledge no study has yet investigated the independent contributions of body weight and local muscle size (crosssectional area, CSA) to the site-specific bone strength of the arm and leg within the same individuals.…”
Section: Ré Sumémentioning
confidence: 99%
“…The biomechanical influences of muscles on bones as assessed by mass/mass relationships are blunted by natural morphogenetic associations [13][14][15][16][17][18], yet there is some evidence of a direct, mechanical interaction [19][20][21][22][23]. In fact, DXA studies of the whole-body and limbs (standard determinations of lumbar spine, femur, and radius are unsuitable for this purpose) have shown that mineral (BMC, y) and lean (related to muscle, x) masses are linearly related in both sexes at any age with similar slopes [24][25][26][27][28][29] (Fig.…”
Section: Imaging Muscle/bone Mass/mass (Anthropometric) Relationshipsmentioning
confidence: 99%
“…Hemos sido pioneros en demostrar que el uso de la fuerza muscular regional es el componente independiente más relevante del entorno mecánico para la determinación de la eficiencia direccional del diseño de los huesos que afecta (2,3,34,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). La gráfica de la relación hueso/músculo puede estandarizarse para cuantificar el grado relativo de participación de factores mecánicos (tracción/ compresión/torsión/flexión de los huesos por la musculatura) y endocrino-metabólicos en cualquier osteopenia, con proyección terapéutica (111)(112)(113)(114)(115)(116)(117). Pueden correlacionarse indicadores de masas ósea y muscular empleando DXA (CMO y masa magra, correlativa de la muscular (118)), o índices de resistencia ósea y fuerza estimada (área de corte) muscular regional empleando QCT o, mejor, pQCT (101-105), y también datos directos, dinamométricos, de fuerza muscular.…”
unclassified